2015
DOI: 10.17957/ijab/15.0078
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously Applied Gibberellic Acid, Indole Acetic Acid and Kinetin as Potential Regulators of Source-Sink Relationship, Physiological and Yield Attributes in Rice (Oryza sativa) Genotypes under Water Deficit Conditions

Abstract: To cite this paper: Khan, S.U., A.R. Gurmani, Jalal-Ud-Din, A. Qayyum, K.S. Abbasi, M. Liaquat and Z. Ahmad, 2016. Exogenously applied gibberellic acid, indole acetic acid and kinetin as potential regulators of source-sink relationship, physiological and yield attributes in rice (Oryza sativa) genotypes under water deficit conditions. AbstractRice is one of the important cereal crops drastically affected by water scarcity in rice ecosystems. In a pot study, the impact of externally applied gibberellic acid (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The soluble protein in R30 significantly increased after rubbing stimulation. Plants adapt to stress by increasing their soluble protein levels [46].…”
Section: Discussionmentioning
confidence: 99%
“…The soluble protein in R30 significantly increased after rubbing stimulation. Plants adapt to stress by increasing their soluble protein levels [46].…”
Section: Discussionmentioning
confidence: 99%
“…(Lum et al, 2010). Destructing unsaturated fatty acids peroxides produces Malonyl dialdehyde as an indicator to determine stress damage, and the intensity of oxidative damage to the lipids plant cell memberans (Khan et al, 2016). In working with Dendrobium mononiliforme under drought stress, Xiaolu et al (2016) reported that peroxidase activity and (Malonyl dialdehyde) content were significantly increased in the leaves under some treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In working with Dendrobium mononiliforme under drought stress, Xiaolu et al (2016) reported that peroxidase activity and (Malonyl dialdehyde) content were significantly increased in the leaves under some treatments. Osmolites such as proline also are effective to stimulate the tolerance to water deficiency caused by drought stress (Khan et al, 2016). Relative water content may provide an equilibrium between the plant water content and leaf transpiration rate more efficiency than the other components reflecting the water relations (Assah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations